2020
DOI: 10.2337/dc19-2177
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Endogenous Glucose Production With SGLT2 Inhibition Is Unchanged by Renal Denervation and Correlates Strongly With the Increase in Urinary Glucose Excretion

Abstract: Sodium-glucose cotransporter 2 (SGLT2) inhibition causes an increase in endogenous glucose production (EGP). However, the mechanisms are unclear. We studied the effect of SGLT2 inhibitors on EGP in subjects with type 2 diabetes (T2D) and without diabetes (non-DM) in kidney transplant recipients with renal denervation. RESEARCH DESIGN AND METHODSFourteen subjects who received a renal transplant (six with T2D [A1C 7.2 6 0.1%] and eight non-DM [A1C 5.6 6 0.1%) underwent measurement of EGP with [3-3 H]glucose infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…In a recent study we showed that, in kidney transplanted individuals with and without type 2 diabetes, administration of a single dose of dapagliflozin was associated with a compensatory increase in EGP [6]. This is indicative of a minor role for kidney innervation in modulating the liver adaptative response.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a recent study we showed that, in kidney transplanted individuals with and without type 2 diabetes, administration of a single dose of dapagliflozin was associated with a compensatory increase in EGP [6]. This is indicative of a minor role for kidney innervation in modulating the liver adaptative response.…”
Section: Discussionmentioning
confidence: 86%
“…Kidney transplantation offers another model of kidney denervation. We have recently assessed the effect of administration of 10 mg dapagliflozin or placebo after an overnight fasting in 14 individuals (six with type 2 diabetes and eight without diabetes) who received a renal transplant [6]. In both diabetic and non-diabetic transplanted individuals, SGLT2 inhibitor-mediated stimulation of EGP was still fully apparent.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in rates of endogenous glucose production, which have been documented in rodents (53,89,90) and humans (50,51,91,92), are an expected consequence of the increases in plasma glucagon concentrations that have been documented following acute and chronic SGLT2 inhibitor treatment. The increase in plasma glucagon following treatment with an SGLT2 inhibitor, which data reviewed in the previous section argue does not occur due to a direct effect on the a-cell, has been attributed to the glucoselowering effect of these drugs (94) and may also be attributable to a direct effect of SGLT2 inhibition in the ventromedial hypothalamus (VMH), the activity of which has been shown to be critical to the hormonal counterregulatory response to hypoglycemia (95).…”
Section: Wat Lipolysis and Sglt2 Inhibitor-induced Euglycemic Ketoacimentioning
confidence: 99%
“…WAT lipolysis promotes ketone production by supplying fatty acids which generate bhydroxybutyrate, acetoacetate and acetone as they are oxidized, and increase gluconeogenesis due to increased supply of both glycerol [a gluconeogenic precursor that drives gluconeogenesis by a substrate push mechanism (79-81)] and acetyl-CoA [the end product of boxidation and an allosteric activator of the ratecontrolling gluconeogenic enzyme pyruvate carboxylase (82)(83)(84)]. Given that both ketogenesis (44,53,(85)(86)(87)(88) and increased rates of endogenous glucose production (51)(52)(53)(89)(90)(91)(92) are observed after SGLT2 inhibitor treatment in humans and rodents, increased rates of lipolysis are a logical upstream explanation of both phenomena. Indeed, in a recent study, we observed that dapagliflozin more than doubled rates of in vivo WAT lipolysis in awake rats (53).…”
Section: Wat Lipolysis and Sglt2 Inhibitor-induced Euglycemic Ketoacimentioning
confidence: 99%
“…Recently, Solis‐Herrera et al 24 showed a positive correlation between elevated EGP and UGE after a single dose of dapagliflozin in post‐renal transplant patients with and without type 2 diabetes. An animal study consistently demonstrated a positive association between EGP and UGE 25 .…”
Section: Discussionmentioning
confidence: 99%